Autocrine Tnf signaling favors malignant cells in myelofibrosis in a Tnfr2-dependent fashion. Issue 11 (November 2018) - Heaton, William; Senina, Anna; Pomicter, Anthony; Salama, Mohamed; Clair, Phillip; Yan, Dongqing; Bell, Russell; Gililland, Jeremy; Prchal, Josef; O'Hare, Thomas; Deininger, Michael
Abstract Tumor necrosis factor alpha (TNF) is increased in myelofibrosis (MF) and promotes survival of malignant over normal cells. The mechanisms altering TNF responsiveness in MF cells are unknown. We show that the proportion of marrow (BM) cells expressing TNF is increased in MF compared to controls, with the largest differential in primitive cells. Blockade of TNF receptor 2 (TNFR2), but not TNFR1, selectively inhibited colony formation by MF CD34+ and mouse JAK2V617F progenitor cells. Microarray of mouse MPN revealed reduced expression of X-linked inhibitor of apoptosis (Xiap ) and mitogen-activated protein kinase 8 (Mapk8 ) in JAK2V617F relative to JAK2WT cells, which were normalized by TNFR2 but not TNFR1 blockade.XIAP andMAPK8 were also reduced in MF CD34+ cells compared to normal BM, and their ectopic expression induced apoptosis. UnlikeXIAP, expression of cellular IAP (cIAP) protein was increased in MF CD34+ cells. Consistent with cIAP's role in NF-κB activation, TNF-induced NF-κB activity was higher in MF vs. normal BM CD34+ cells. This suggests that JAK2V617F reprograms TNF response toward survival by downregulating XIAP and MAPK8 through TNFR2. Our results reveal an unexpected pro-apoptotic role for XIAP in MF and identify TNFR2 as a key mediator of TNF-induced clonal expansion.